PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI, KOMITMEN ORGANISASI, DAN SISTEM PENGENDALIAN INTERNAL TERHADAP PENGELOLAAN DANA DESA (STUDI PADA KECAMATAN DI KABUPATEN KAMPAR) - Aulia Rahman; Meilda Wiguna; Nanda Fito Mela (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2026)
This study examines the influence of human resource competency, informationtechnology utilization, organizational commitment, and internal control systemson village fund management in sub-districts in Kampar Regency. Thisquantitative study employed a survey method involving 348 village officialsselected using convenience sampling. Data were analyzed using SPSS 2026. Theresults indicate that information technology utilization, organizationalcommitment, and internal control systems have a significant positive influence onaudit considerations, while human resource competency does not significantlyinfluence audit considerations. The model explains 52.2% of the variance invillage fund management. This study contributes to the literature on village fundmanagement and provides practical implications for improving the quality ofvillage fund management.Keywords: village fund management; human resource competency; informationtechnology utilization; organizational commitment; internal control systems